2020
DOI: 10.1029/2019wr026108
|View full text |Cite
|
Sign up to set email alerts
|

Value of Crowd‐Based Water Level Class Observations for Hydrological Model Calibration

Abstract: While hydrological models generally rely on continuous streamflow data for calibration, previous studies have shown that a few measurements can be sufficient to constrain model parameters. Other studies have shown that continuous water level or water level class (WL‐class) data can be informative for model calibration. In this study, we combined these approaches and explored the potential value of a limited number of WL‐class observations for calibration of a bucket‐type runoff model (HBV) for four catchments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…For the other catchments with a high flashiness index (A6 and A9), the high flows were also captured well (10 and 13% of the observations at times when the water level was higher than the 90th percentile, respectively). A (small) bias in high flow observations can be beneficial for hydrological model calibration based on WL‐class data (Etter, Strobl, Seibert, & van Meerveld, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the other catchments with a high flashiness index (A6 and A9), the high flows were also captured well (10 and 13% of the observations at times when the water level was higher than the 90th percentile, respectively). A (small) bias in high flow observations can be beneficial for hydrological model calibration based on WL‐class data (Etter, Strobl, Seibert, & van Meerveld, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a first test, Strobl, Etter, van Meerveld, and Seibert (2019a) asked passers‐by at 10 river locations in Switzerland to estimate both the streamflow and the water level class based on the virtual staff gauge (hereafter shortened to WL‐class) and quantified the errors of these estimates. These errors were later used to create synthetic streamflow and WL‐class time series in two model studies to explore the potential value of such data for model calibration (Etter, Strobl, Seibert, & van Meerveld, 2020; Etter, Strobl, Seibert, & van Meerveld, 2018. These studies showed that the estimates of streamflow were not accurate enough to be informative for hydrological model calibration, but that WL‐class estimates significantly improved model performance compared to the situation without any data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation data, obtained in a flood extent survey involving 44 community member's reporting on flood depths a few hours after the simulated rainfall event, proved to be valuable to validate flood modeling results. Earlier studies have shown that community observations provide a valuable source of information for flood risk analysis (Paul et al, 2018;Etter et al, 2019;Strobl et al, 2019). Even if the amount of data collected through flood surveys is small and the uncertainty of the flood depth classes cannot be quantified, the data still provides an effective form of validation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, validation data to evaluate the performance of flood models is often missing. Previous research suggests that citizen observations offers an alternative data source in data-scarce environments to estimate water levels for model calibration (Etter et al, 2019;Strobl et al, 2019). Hence, we propose a framework for acquisition of drainage data and water levels required for flood model development and validation through community mapping.…”
Section: Introductionmentioning
confidence: 99%